Radial wrinkling of viscoelastic film-substrate systems. (1st August 2022) - Liu, Xiao; Liu, Ying; Feng, Xi-Qiao
Abstract: In this paper, the radial local wrinkling triggered by a homogeneous pre-stretch in a circular area of the film in a viscoelastic bilayer system is studied. The stress relaxations in the film and the substrate are described by the Boltzmann viscoelastic model. The critical condition for the wrinkling of the viscoelastic bilayer system is firstly established. Then the influence of the film/substrate viscosity ratio and normalized moduli on the system instability, as well as the temporal evolution of the wrinkling mode, is discussed. The phase diagram for the regulation of the circumferential wrinkling wavenumber is obtained. This work provides an effective method for buckling analysis in soft matter system in which the components are ordinarily viscoelastic, and small viscosity variation may have large influences on pattern selection and morphology evolution.